2000
DOI: 10.1002/1521-396x(200004)178:2<811::aid-pssa811>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Charge Injection Mechanisms in Solid State Organic Light-Emitting Devices Based on Alizarin Violet

Abstract: Light-emitting devices utilizing a dye-insulating matrix blend have been fabricated. The emitting dye material used was alizarin, while poly(methylmethacrylate) has been used as the insulating matrix material. Current±voltage and luminance±current characteristics have been studied for different molar concentrations of alizarin. Luminance has been observed in both bias directions in devices with lower alizarin concentration. Luminance under forward bias has been independent of alizarin molar concentration, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…This means that the SCLC mechanism, shown by impedance spectroscopy for V > 1 V, could not be the main one. Several authors have shown [55,56], for PVK sandwich structures, that in the low field domain, thermionic emission can occur. This is presently verified over a broad voltage domain, as shown in the inset of figure 9 for 20% volume ratio of TiO 2 nanoparticles (the same behaviour is observed for 30 and 50%).…”
Section: Forward Biasmentioning
confidence: 99%
“…This means that the SCLC mechanism, shown by impedance spectroscopy for V > 1 V, could not be the main one. Several authors have shown [55,56], for PVK sandwich structures, that in the low field domain, thermionic emission can occur. This is presently verified over a broad voltage domain, as shown in the inset of figure 9 for 20% volume ratio of TiO 2 nanoparticles (the same behaviour is observed for 30 and 50%).…”
Section: Forward Biasmentioning
confidence: 99%
“…We first present our studies that have been obtained for different contacts/electrodes. By keeping electron-barrier height, e f , unchanged ͑0.7 eV͒, 17 we varied the hole-barrier height, h f , to study the EL profile. Figure 1 shows the dependence of EL f and EL r on h f .…”
Section: Resultsmentioning
confidence: 99%
“…Under forward bias, the barrier height for holes ( h f ) and electrons ( e f ) have been considered as 0.3 and 0.7 eV, respectively. 17 The lattice plane next to the ITO electrode is considered as zϭ0, while the one adjacent to Al is zϭz max .…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…The barrier heights for holes and electrons were taken ͑as 0.4 and 0.6 eV, respectively͒ from our recent experimental results. 20 Hole-toelectron mobility ratio ( h / e ) and ␤ have been taken as 30 and 0.01, respectively. The similarity between the experiment and simulation primarily confirms the hypothesis we put forward in the transient response studies.…”
Section: Resultsmentioning
confidence: 99%